Impact of Plasma and Thermal Treatment on the Long-term Performance of Vanadium Redox Flow Electrodes – Significance of Surface Structure vs Oxygen Functionalities. Issue 7 (28th July 2021) - Greese, Tobias; Loichet Torres, Paulette A.; Menga, Davide; Dotzauer, Petra; Wiener, Matthias; Reichenauer, Gudrun
Abstract : Graphite felt (GF) electrodes of vanadium redox flow batteries show enhanced performance when thermally treated before their assembly. Thermal treatment works by simultaneously increasing electrode wettability, kinetic activity, and total surface area (TSA). This study examines these performance determining yet inseparable effects, especially considering the electrodes' long-term operation. We exposed GF electrodes to 5 min plasma treatment, ensuring equal wettability, and thermally treated them in air at 400 °C for different durations. We then linked the resulting GF surface structure with the electrode performance, monitored with a high temporal resolution, and controlled electrolyte conditions. The performance, expressed in charge-transfer resistances and voltage efficiencies, correlated accurately with the thermal treatment times. According to XPS, against expectation, the thermal treatment decreased the number of surface oxygen functionalities. Instead, SEM and krypton adsorption revealed that the surface had become rougher, and the TSA increased. Upon corrosion, the surface presumably exposed more carbon edge sites being catalytically active, explaining the improved performance. Therefore, compared with the commonly suggested surface oxygen enrichment, increasing the GF surface roughness and TSA may be the more promising strategy to enhance and stabilize the long-term VRF electrode performance.